Coupling optimization study of key influencing factors on PCM trombe wall for year thermal management. (1st December 2021) - Zhu, Na; Deng, Renjie; Hu, Pingfang; Lei, Fei; Xu, Linghong; Jiang, Zhangning
Abstract: The proposed environment-interactive novel Trombe wall system was a passive building envelope integrated with phase change material (PCM) based on traditional Trombe wall. Compared with traditional Trombe wall system, this system can make full use of solar energy and nature ventilation, improving indoor thermal comfort. The dynamic heat transfer model of PCM Trombe room was established, and six key factors influencing thermal performance of PCM Trombe wall system were analyzed. Through the coupled operation of TRNSYS heat transfer model and GenOpt optimization software, the energy consumption characteristics of the system and the optimal value of the key influencing factors were analyzed and obtained. The optimal air gap thickness was 0.05 m, the optimal external sun-shading length was 0.78 m, the optimal thermal storage wall thickness was 0.68 m, the optimal vents area was 0.6 m 2, the optimal melting temperature of lower temperature PCM layer was 16.5 °C, and the optimal melting temperature of higher temperature PCM layer was 27.75 °C. The annual total building load was reduced by 7.56% in optimized reference Trombe room compared with traditional Trombe wall, and the annual total building load was reduced by 13.52% in optimized PCM Trombe compared with reference Trombe wall. Highlights: A novel environment-interactive PCM Trombe wall was proposed. Double-layer PCM was used for whole year thermal management. Multiple parameters were coupled and optimized by GenOpt based on TRNSYS. Three typical types of Trombe wall were fully compared and analyzed.